Novel Nexus with NFκB, β-catenin, and RB1 empowers PSMD10/Gankyrin to counteract TNF-α induced apoptosis establishing its oncogenic role. (May 2022) - Mulla, Saim Wasi; Venkatraman, Prasanna
Abstract: NFκB is a critical rapid-acting transcription factor that protects cancer cells from programmed cell death induced by stress or therapy. While NFκB works in nexus with non-classical oncoproteins such as STAT3 and AKT under a variety of conditions, it is a major antiapoptotic factor activated by TNF-α of the tumor microenvironment. Therefore, it is surprising that PSMD10, an oncoprotein overexpressed in several cancers and a marker of poor prognosis, is reported to inhibit the NFκB pathway. In this study, we explore the role of PSMD10 in cancer cells exposed to TNF-α. We screen several breast and colon cancer cell lines and select SW480, a colon cancer cell line highly resistant to TNF-α, and demonstrate that PSMD10 knockdown sensitizes these cells to TNF-α induced cell death. One of the mechanisms involves transcriptional regulation of β-catenin and RB1, two key colon cancer cell specific anti-apoptotic factors. Surprisingly, we find that PSMD10 is required for optimal phosphorylation and transcriptional activation of NFκB (RELA). Thus, upon PSMD10 knockdown, there is significant downregulation of anti-apoptotic NFκB target genes TNFAIP3 ( A20), BIRC2 (cIAP1), BIRC3 (cIAP2), and XIAP . Our study, for the first time, shows that PSMD10 is required for the activation of the pro-survival arm via NFκB transcriptional activation to prevent cancer cells from succumbing to TNF-induced cell death. In addition by transcriptional regulation of two major antiapoptotic players RB1 and β-catenin, PSMD10 proves to be a coveted oncoprotein with a key role in tumorigenesis. Graphical Abstract: ga1 Highlights: PSMD10 knockdown sensitizes SW480 colon cancer cell line to TNF-α induced cell death. PSMD10 knockdown decreases β-catenin and RB1 levels in SW480 cells. PSMD10 regulates NFκB dependent transcription of anti-apoptotic genes in SW480 cells.